2016
DOI: 10.1186/s13027-016-0102-9
|View full text |Cite
|
Sign up to set email alerts
|

Invasive cervical cancers in the United States, Botswana and Kenya: HPV type distribution and health policy implications

Abstract: BackgroundMore deaths occur in African women from invasive cervical cancer (ICC) than from any other malignancy. ICC is caused by infection with oncogenic types of human papillomavirus (HPV). Co-infection with the human immunodeficiency virus (HIV) accelerates the natural history of ICC, and may influence the HPV type distribution. Because HPV vaccines are available, this malignancy is theoretically preventable, but the vaccines are largely type-specific in protection against infection. Data on specific HPV ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(37 citation statements)
references
References 19 publications
(28 reference statements)
2
28
2
1
Order By: Relevance
“…Unlike in the previous studies done on cervical cancer, [ 27 , 29 , 30 ], HPV 18 was not detected in our study. We also observed HPV types; 26, 31, 45, 51, 66 and 68, which have not been previously reported.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Unlike in the previous studies done on cervical cancer, [ 27 , 29 , 30 ], HPV 18 was not detected in our study. We also observed HPV types; 26, 31, 45, 51, 66 and 68, which have not been previously reported.…”
Section: Discussioncontrasting
confidence: 99%
“…MacLeod et al , [ 30 ] reported 64% hr.-HPV prevalence in HIV-infected women with similar cervical lesions, and in another study, of HIV positive women with invasive cervical cancer (ICC), the prevalence of hr.-HPV was 95% [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…No single study related to the current systematic review was accessed from Eretria, Djibouti, Somalia, and South Sudan. Of the four studies included, two studies were from Ethiopia [20,21] and one from Kenya [22]. While, one study was investigated the genotyping of human papilloma virus in paraffin embedded cervical tissue samples from women in Ethiopia and the Sudan [23], this particular study, therefore, was selected for the current review as for Ethiopia and Sudan.…”
Section: Description Of Study Setting and Sample Sizementioning
confidence: 99%